Information and Communication technology for sustainable development in Nigeria: hope or hype (2005)
The increasing diffusion and adoption of Information and Communication Technologies as tools for development activities is impacting positively on the economics of most nations so much that access to and utilization of the technologies have now become one of the determining factors in the categorization of nations into developed and developing. The disparity in the capacity to access and apply the technologies among nations is referred to as digital divide. Efforts at bridging this divide perhaps explain the worldwide move by nations to put in place policies as mechanism for developing their capacity, adopting and utilizing the technologies thereby availing themselves of the opportunities presented by the global information superhighway, including membership of the information society. Nigeria accordingly in the year 2001 put in place the National Policy for Information Technology with a mission statement to make the country an active player in the information society, including using the technology as an engine for sustainable development and global competitiveness. The paper thus, takes a critical look at the policy with regard to its suitability or otherwise to attain the set policy objectives of utilizing ICTs for sustainable economic development, delivery of social services across the different sectors of the economy and membership of the global information society. The policy is analyzed in the context of the country’s growing development challenges. The paper concludes that the policy though, a reactive one for that matter is nevertheless capable of making Nigeria an ICT-driven society provided the issues of synergy and resource allocation are addressed at the level of implementation